Surface integrity of titanium when machining with various cutting parameter - Mohd 'Azim, Ab. Halim (2010)
A comprehensive study of the surface integrity of the machine workpiece in the CNC machine of titanium with various cutting parameter is presented in this thesis. Polycrystalline diamond brazed into carbide substrated as the tools in this research.. For machining tests, all of the machining experiments were carried out by using ROMI C420 CNC turning machine. The machining parameters that will be manipulated in this experiment are feed rate and cutting speed. The surface roughness of the bar will be measured by using perthometer Surfcom 130A and chip hardness will be measure by using Micro Vickers Hardness test. The data is analyzed in STATISTICA and manually plot in excel.